Pelatihan dan Analisis Sistem Informasi Risiko dan Pengendalian Kualitas pada Pengembangan Perangkat Lunak di PT. Extramarks Education Indonesia - Bersello , Ruben; Putri, Fiqrotul Aulia; W, Raditya Galih (Yayasan Bina Internusa Mabarindo, 2025)
In the digital transformation era, managing risks and quality control in software development has become crucial for the success of technology products, particularly in the education sector. This training aimed to enhance participants' understanding of risk information system analysis and quality control in the development of